2022
DOI: 10.1002/chem.202201123
|View full text |Cite
|
Sign up to set email alerts
|

Cover Feature: Anomeric Stereoauxiliary Cleavage of the C−N Bond of d‐Glucosamine for the Preparation of Imidazo[1,5‐a]pyridines (Chem. Eur. J. 29/2022)

Abstract: The Gänseliesel showcases the scientific magic in Göttingen! Scientific magic on the α‐anomer of d‐glucosamine helps the targeted cleavage of C−N bonds in d‐glucosamine (α‐2° amine) from biobased resources and the conjunction of nitrogen in the synthesis of imidazo[1,5‐a]pyridines. This new approach expands the scope of readily accessible imidazo[1,5‐a]pyridines relative to existing state‐of‐the‐art methods. A key strategic advantage of this approach is that the α‐anomer of d‐glucosamine enables C−N bond cleav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The results revealed that amino acids, e.g. glycine 3i (56%) 37 and (tert-butoxycarbonyl)-L-valine 3h (57%), 38 were noticeably superior to D-glucosamine 3a (27%), 36 1,3,4,6-tetra-O-acetyl-2-amino-2-deoxy-β-D-glucosamine 3b (35%), 27 1,3,4,6-tetra-O-acetyl-2-amino-2-deoxy-α-D-glucosamine 3c (25%), 27 (S)-diphenyl( pyrrolidin-2-yl)methanol 3d (21%), 39 (S)-2-(diphenyl((trimethylsilyl)oxy)methyl)pyrrolidine 3e (30%), 39 L-proline 3f (32%), 23 and (5S)-(−)-5-benzyl-2,2,3-trimethylimidazolidin-4-one 3g (45%). 24 Besides, leucine with D/ L-tert-butyl bulk steric hindrance did not obviously affect the reaction activity, such as that of 3j (58%) and 3k (53%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that amino acids, e.g. glycine 3i (56%) 37 and (tert-butoxycarbonyl)-L-valine 3h (57%), 38 were noticeably superior to D-glucosamine 3a (27%), 36 1,3,4,6-tetra-O-acetyl-2-amino-2-deoxy-β-D-glucosamine 3b (35%), 27 1,3,4,6-tetra-O-acetyl-2-amino-2-deoxy-α-D-glucosamine 3c (25%), 27 (S)-diphenyl( pyrrolidin-2-yl)methanol 3d (21%), 39 (S)-2-(diphenyl((trimethylsilyl)oxy)methyl)pyrrolidine 3e (30%), 39 L-proline 3f (32%), 23 and (5S)-(−)-5-benzyl-2,2,3-trimethylimidazolidin-4-one 3g (45%). 24 Besides, leucine with D/ L-tert-butyl bulk steric hindrance did not obviously affect the reaction activity, such as that of 3j (58%) and 3k (53%).…”
Section: Introductionmentioning
confidence: 99%
“…We propose herewith that a weak-coordination-auxiliary strategy involving an aminocatalyst would help overcome the challenges, especially the energy barrier in the intramolecular cyclization step. With our ongoing interest in the carboxylate assisted activation strategy [31][32][33][34] and the preparation of N-heterocyclic compounds by sustainable organic synthesis methods, 27,35,36 herein, we report for the first time glycine-catalyzed [3 + 2] cyclization of α,β-unsaturated ketones and N-heteroaryl ketones for various 2-acylindolizines by a weak-coordination-auxiliary strategy (Scheme 1d).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, carbohydrates as the most abundant and renewable biomass with native chiral backbones have been widely utilized as carbohydrate-derived ligands for enantioselective reactions [37][38][39] , whereas aminocatalyst derived from amino sugars has received less attention so far 40,41 . Inspired by our recently work on anomeric stereoauxiliary cleavage of the C−N bond of glucosamine for the efficient preparation of imidazo[1,5-a]pyridines 42 , we discovered a novel sustainable aminocatalysis strategy via recyclable stereoauxiliary combined with iminium ion/enamine tandem sequence as potential synthesis strategy (Fig. 1d).…”
mentioning
confidence: 99%
“…C–N bond cleavage in certain primary amines, namely benzylamines 4 and allylic amines, 5 has been reported frequently. In contrast, C–N bond cleavage in other simple primary amines has been less extensively investigated, 6 perhaps due to their high C–N bond dissociation energy levels. Therefore, the C–N bond cleavage of such molecules is rarely hard and remains quite challenging.…”
mentioning
confidence: 99%